The Determinants of In-Migration of the Risen Population Between Provinces in Indonesia - Gustari, Mifthaqul Fani; Arif, Muhammad (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research aims to estimate the direction and magnitude of the influence of the elasticity of job opportunities, the provincial minimum wage, the average length of schooling, the Gross Regional Domestic Product (GRDP) of the primary sector, the GRDP of the secondary sector, and the GRDP of the tertiary sector on the inflow of migration using data from 33 provinces in Indonesia from 2010 to 2022. Methodology: This study employs a quantitative approach with a panel data regression method. The data is secondary data sourced from the Central Bureau of Statistics (BPS). The analytical tool used is regression analysis using Eviews software. Results: The results indicate that the provincial minimum wage and the GRDP of the secondary sector have a negative and significant impact on migration inflow. The average length of schooling, the GRDP of the primary sector, and the GRDP of the tertiary sector positively and significantly affect migration inflow. Meanwhile, the elasticity of job opportunities does not impact migration inflow. Applications/Originality/Value; The government can play an important role in managing migration related to the elasticity of job opportunities, the provincial minimum wage, the average length of schooling, and the GRDP. The government can use this study’s findings to plan strategies related to population distribution in Indonesia, ensuring that population density does not occur only in certain areas and that the economy in each province can be balanced.